Reward anticipation revisited: evidence from an fMRI study in euthymic bipolar I patients and healthy first-degree relatives - Kollmann, Bianca; Kirsch, Peter (Journal of affective disorders, 2017)
Background: Symptomatic phases in bipolar disorder (BD) are hypothesized to result from a hypersensitive behavioral activation system (BAS) being sensitive to potential rewards. However, studies on the neuronal underpinnings of reward anticipation in BD are scarce with contradictory findings and possibly confounded by effects of dopaminergic medication, necessitating further research on dysfunctional motivation in BD. Moreover, its role as vulnerability marker for BD is unclear. Methods: Functional imaging was conducted in 16 euthymic BD-I patients free from dopaminergic medication and 19 healthy first-degree relatives using a monetary incentive delay task and compared to parallelized control groups. Further, reward proneness, using the BIS/BAS questionnaire, and its relationship to neural reward anticipation was investigated. Results: BD-I patients displayed greater anterior cingulate cortex (ACC) activity during reward anticipation and higher BIS total scores compared to controls, with a positive relationship between the two measures. There were no neural or self-report group differences between relatives and controls. Limitations: Due to the experimental design, the role of the ACC during receipt of reward remains unknown, sample sizes were rather small, and patients were not naïve to dopaminergic drugs, making an exclusion of medication effects on findings impossible. Conclusions: Our findings give new insights on reward anticipation in BD. BD-I patients rated themselves as more risk avoidant and showed larger recruitment of the ACC rather than ventral striatum compared to controls during reward anticipation, possibly to down-regulate hyperactive limbic reward regions. This activation seems to be a consequence of rather than a vulnerability marker for the disorder.